2000
DOI: 10.1016/s0042-6989(00)00072-9
|View full text |Cite
|
Sign up to set email alerts
|

A new visual illusion of relative motion

Abstract: We present a remarkably simple illusion that manifests whenever a certain class of flat static patterns are moved across our peripheral visual field. A relative motion is perceived in a direction perpendicular to the true motion. Translatory, looming, and rotational movements of the head or the pattern can all elicit it. Each pattern is constructed of simple elements that define, through luminance, an orientation polarity. This polarity could be encoded by spatiotemporally tuned, orientation sensitive units in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
66
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 12 publications
8
66
0
3
Order By: Relevance
“…Motion illusion is a type of visual illusion in which we perceive motion that is different (in direction, strength, etc 789101112131415.…”
mentioning
confidence: 99%
“…Motion illusion is a type of visual illusion in which we perceive motion that is different (in direction, strength, etc 789101112131415.…”
mentioning
confidence: 99%
“…An equally widespread pattern in Roman mosaics reveals a completely different effect. A presentation at the ECVP in 2011 showed that the Romans certainly already knew about the Pinna-Brelstaff illusion (Lingelbach & Wade, 2011;Pinna & Brelstaff, 2000).…”
Section: The Conceptmentioning
confidence: 99%
“…Kitaoka and Ashida (2007) reviewed the illusions and classified them in two categories; some of them are classified as “illusory motion in a direction different from the retinal-image motion,” i.e. producing perception of motion components at a right-angle direction to the retinal-motion direction (Gori & Hamburger, 2006; Ito, Anstis, & Cavanagh, 2009; Pinna & Brelstaff, 2000). The other illusions category is “illusory motion in the direction parallel to the retinal-image motion.” For example, the swinging-motion illusion (Khang & Essock, 2000) produces illusory motion arising in an opposite direction to eye movement direction.…”
Section: Introductionmentioning
confidence: 99%
“…the same direction as the pursuit eye movement), (2) the centre disc does not move when the sheet on which the radial patterns are printed is rotated (illusory stillness against physical motion, see also Figure 2 in Ito, 2012), (3) the effect does not change with pursuit direction (no anisotropy in the effect) because the radial pattern has virtually no orientation and (4) despite the radial stimulus configuration, this illusion needs one-dimensional retinal motion, not expansion/contraction of the stimulus pattern (e.g. “Pinna and Brelstaff illusion,” Pinna & Brelstaff, 2000; “the Rotating-Tilted-Line illusion,” Gori & Hamburger, 2006; “the Breathing Light Illusion,” Gori & Stubbs, 2006; “the accordion grating illusion,” Gori, Giora, Yazdanbakhsh, & Mingolla, 2011). This is also different from those that do not need explicit physical motion of the stimulus image (e.g.…”
Section: Introductionmentioning
confidence: 99%